Usulan Perancangan Fasilitas Kerja untuk Mencegah Keluhan Musculoskeletal Disorders pada Karyawan Menggunakan Pendekatan Anthropometri - Marfuah, Hasti Hasanati; Regita Ayu Permana Putri (Program Studi Teknik Industri, Fakultas Sains dan Teknologi, Universitas Widya Mataram, 2025)
Musculoskeletal Disorders are one of the occupational health and safety disorders. In applying the principles of ergonomics, anthropometric measurements are needed. The anthropometric approach is used to measure the dimensions of the human body in designing work aids so as to provide comfort to employees when doing work. This research was conducted to provide proposals for designing work facilities by considering several factors, namely the subject of workers and complaints of Musculoskeletal Disorders. The result of this research is a proposed work facility design consisting of ergonomic chairs, tables and trolleys with an anthropometric approach. The anthropometric data used are sitting shoulder height (tbd), popliteal height (tpo), popliteal buttocks (pp), shoulder width (lb), hip width (lp), forward hand reach (jtd), hand stretch (rt), sitting elbow height (tsd), standing elbow height (tsd), and diameter of hand circumference (dlg). Before the improvement, employees experienced an increase in complaints of musculoskeletal disorders by 14.6%. Meanwhile, after the improvement, employees experienced a decrease in complaints of musculoskeletal disorders by 6.4%. In addition, there was an increase in production by 4%.